2012
DOI: 10.1097/nmd.0b013e31826b6ecc
|View full text |Cite
|
Sign up to set email alerts
|

Coping Skills, Mental Disorders, and Suicide Among Rural Youths in China

Abstract: The strain theory of suicide postulates that psychological strains usually precede mental disorders including suicidal behavior. Lack of coping skills is one of the four strains. This article focuses on the effect of lack of coping skills on individual mental disorders and suicide. Data including 392 suicide cases and 416 community-living controls were from a large psychological autopsy study conducted in rural China. The Hamilton Depression Rating Scale and the Structured Clinical Interview for DSM-III-R were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…We used its 24 items to assess coping skills and the choices range from 1=not at all to 4=fairly often. The previous studies have indicated the high validity of the CRI scale in the West (Agnew & Kaufman, 2010; Doveston & Cullingford-Agnew, 2006) and the East (Li & Zhang, 2012) samples.…”
Section: Methodsmentioning
confidence: 95%
“…We used its 24 items to assess coping skills and the choices range from 1=not at all to 4=fairly often. The previous studies have indicated the high validity of the CRI scale in the West (Agnew & Kaufman, 2010; Doveston & Cullingford-Agnew, 2006) and the East (Li & Zhang, 2012) samples.…”
Section: Methodsmentioning
confidence: 95%
“…For the social structural influences, social support was a protective factor (Lyu and Zhang, 2014) as found elsewhere in the world (Thoits, 1986), but being married (Zhang et al, 2010b) and religious belief (Zhang and Xu, 2007) were correlates (Kraemer et al, 1997) which were starkly different from the evidence in the West (Stack, 1983, 1998). Further, less education, low SES, family suicide history, negative life events, and deficient coping were also found to be significantly associated with an increased risk of suicide among those rural young residents in China (Jia and Zhang, 2011; Kong and Zhang, 2010; Li and Zhang, 2012; Liu and Tein, 2005; Zhang and Ma, 2012) (Please review the information in Table 1 and Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…The total score was used in the analyses with higher score indicating better coping skills. It has been tested multiple times in rural Chinese populations with excellent reliability and validity (Li and Zhang, 2012; Zhang et al, 2011c). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, higher levels of neuroticism seem to predict future onset of psychotic disorders [41,42]. A large study by Li and Zang showed that patients with suicidal ideations, both with and without psychotic disorders, scored significantly higher on passive coping mechanisms and lower on active coping than the control group [43]. However, studies on neuroticism and coping styles in relation to suicide risk in psychotic patients are lacking.…”
Section: Introductionmentioning
confidence: 99%